Costs in the conservation of hornbills found in Northwest and Central Panay - Dionela, Isagani
This research project sought to determine the costs in the conservation of hornbills found in the Northwest and Central Panay. furthermore, this study aimed to determine the economic policies and strategies implemented by the government and non government sector in the conservation of the hornbills, and to determine the alternative options in coserving the hornbills. The subject were 33 key informants composed of wildlife educators (WE), former poachers (FP), former hunters (FH), forest rangers (FR), community conservationist (CC), heads of the conservation groups (PESCP and BIOCON), and local government officials (LGU officials). The respondents were selected through snowball technique. This technique was used since there was no complete list of respondents. It required the identification of employees under the PESCP and BIOCON who served as wildlife educators, nest wardens (these were former hunters and former poachers), community conservationists and forest rangers. Further, there were certain persons who were once or are still hunters and poachers not belonging to these organizations but whom the researcher believed to be key informants . this descriptive research used a set of researcher-made semi-structured inteview schedule to gather data from the respondents. The interviewer combined the guide questions with new topics that arise during interview bared from the responses. To descibe the data gathered, the research derived a quantitative and qualitative result on the cost of conservation of hornbills in Northwest and Central Panay. For the quantitative analysis, fixed and variable costs were identified per key institution. These cost were drawn out of the set of financial statements issued by some of the institutions and others were divulged by the key informants. The quantitative analysis involves identifying the economic policies and strategies implemented by the key institutions. These institutions were divided into two: non-government sector and the government sector. Alternative options in conserving the hornbills were presented., The results of the investigation showed that the total cost in the conservation of hornbills was Php 26,452,156.50. The total variable cost amounted to Php19,871,868.54 and the total fixed cost amounted to Php 6,580,288. when the cost in the conservation is taken per sector, the non-government sector paid out Php 26,037,012.00 while the government sector spent Php 415,144.54. When the cost in the conservation is taken per institution, PESCP spent Php 22,345,260.00 or 84.5 percent, BIOCON paid out Php 3,691,752.00 or 14 percent , NPBMC expended Php 353144.50 or 1.3 percent, and PAMB spent Php 62000.00 or 0.2 percent of the total cost. The data was computed using Microsoft Excel.